A Randomized Control Study to Compare Postoperative Analgesic Efficacy between USG Guided Erector Spinae Plane Block versus Transverse Abdominis Plane (Tap) Block in Elective Lower Segment Caesarean Section at a Tertiary Care Centre - Shah, Alka; Chandrasekharan, Chandra; Shah, Chiranshi (Academia Anesthesiologica International, 2022)
Background: Aim of present research was to evaluate analgesic effectiveness of ultrasound guided (USG) bilateral ESP block with that of bilateral anterior TAP block in LSCS surgery. Subjects and Methods: Sixty women were planned for elective caesarean deliveries under intrathecal anaesthesia were included in the trial. The women were arbitrarily owed in identical numbers to an ESP group or a TAP group in detach opaque envelopes. Postoperative pain was calculated by the visual analogue scale (VAS) pain score at rest at 0, 4, 8, 12, 24 hours. Results: Significant dissimilarity in median duration of analgesia among the ESP group and the TAP group. The median total tramadol use in the primary 24 hours was significantly superior in the TAP group than in the ESP group. VAS pain scores at rest for repeated measures were 0.3 units lesser on average in the ESP group than in the TAP group during the primary 24 postoperative hours and 0.5 units lower in the ESP group in the first 8 postoperative hours. Conclusion: The ESP block has a extended duration of analgesia, hold-up the time to primary necessity for analgesia, and decrease tramadol utilization compared with the TAP block and can be utilized in multimodal analgesia and opioid free schedules following caesarean section.